Kohiponimia jako relacja z pogranicza kategorii opozycji semantycznej. Perspektywa użytkownika języka polskiego: badanie psycholingwistyczne - Mikołajczak-Matyja, Nawoja Mikołajczak-Matyja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The paper considers the relation of semantic opposition in terms of the prototype theory of concepts. Its purpose is to provide information on peripheral or border areas of the category of semantic opposition. Data from linguistic analyzes, as well as the results of contemporary corpus studies, indicate that pairs of co-hyponyms from multi-element sets are potentially relevant material in peripheral areas of the category of semantic opposition. A psycholinguistic study was conducted to verify the psychological reality of the data. 720 Polish language users were instructed to provide semantic oppositions to the list of 24 stimuli words (test of directed associations). The research material was Polish nouns belonging to 3 lexical fields: animals, plants and artifacts, with no obvious semantic oppositions (as bee, cabbage, vase). It turned out that, according to the hypothesis, proportions of reactions classified as co-hyponyms of stimuli are high: for 21 stimuli it was 52–94% of the response corpora and for 22 stimuli the dominant reaction was co-hyponym of the stimulus word (as cabbage-lettuce, bee-wasp, vase-flowerpot). The characteristics that determine the choice of a given co-hyponym as the semantic opposite of the stimulus were identified. The remainder of the response corpus was analyzed in order to reveal other ways and mechanisms for seeking the semantic opposition by respondents. The data obtained in the presented study confirm the necessity to incorporate the problem of co-hyponymic pairs from multi-element sets into reflections on the category of the semantic opposition.